The Principle of Independence of Multiple Bank Accounts for A Single Client and its Effects in Cases of Bankruptcy and Seizure - Hameed, Riyadh Nadhim; Rafea, Ali Abbas (Journal of Asian Multicultural Research for Social Sciences Study, 2023)
The multiplicity of bank accounts for a single client is a phenomenon observed in most countries, often stemming from financial crises faced by banks. Whether the client is an individual or a legal entity, they have the right to open multiple bank accounts, either within one bank, or across several branches of the same bank, or even in different banks. This gives rise to legal implications. Having multiple bank accounts across different banks generally does not pose any legal issues due to the legal independence of these accounts. However, challenges may arise when opening multiple accounts with the same bank or its branches. Each account is subject to specific rules governing its operation, suspension, and associated transactions. Consequently, there is a variation in the financial returns of these accounts based on their independence, leading to legal implications such as seizure and client bankruptcy. If a client goes bankrupt and has both creditor and debtor accounts, the bank pays the creditor balance in the creditor account to the bankruptcy estate. The bank is treated as a debtor with the debtor account balance and is subject to the division of creditors. This means that the bank cannot offset the creditor side of one account against the debtor side of another account opened by the same client. Moreover, according to the principle of independence, if one of the client's accounts in a bank or its branches is seized, it does not affect other accounts, and the seizure does not extend to them. This is in contrast to situations lacking independence.